The Effect of Mindful Parenting on the Relationship Between Perceived School Difficulties and Depressive Symptoms in a Sample of Portuguese Adolescents - Silva, Patrícia Santos (2023)
Dissertação de Mestrado em Intervenções Cognitivo-Comportamentais em Psicologia Clínica e da Saúde apresentada à Faculdade de Psicologia e de Ciências da Educação